Amorphous Carbon Monolayer: A van der Waals Interface for High-Performance Metal Oxide Semiconductor Devices - Akkili, Viswanath G.; Yoon, Jongchan; Shin, Kihyun; Jeong, Sanghyun; Moon, Ji Yun; Choi, Jun Hui; Kim, Seung Il; Patil, Ashish A.; Aziadzo, Frederick; Kim, Jeongbeen; Kim, Suhyeon; Shin, Dong Wook; et al. (ACS Nano, 2025)
Ultrasmall-scale semiconductor devices (≤5 nm) are advancing technologies, such as artificial intelligence and the Internet of Things. However, the further scaling of these devices poses critical challenges, such as interface properties and oxide quality, particularly at the high-k/semiconductor interface in metal-oxide-semiconductor (MOS) devices. Existing interlayer (IL) methods, typically exceeding 1 nm thickness, are unsuitable for ultrasmall-scale devices. Here, we propose a one-atom-thick amorphous carbon monolayer (ACM) as the IL to address these issues for MOS devices. ACM is disordered, randomly arranged, and short of long-range periodicity with sp2 hybridized carbon network, offering impermeability, van der Waals (vdW) bonding, insulating behavior, and effective seeding layer. With these advantages, we have utilized ACM vdW IL (vIL) in Al2O3/H-Ge MOS capacitors. The interface trap density was suppressed by ∼2 orders of magnitude to 7.21 × 1010 cm-2 eV-1, with no frequency-dependent flat band shift. The slow trap density is decreased to 2 orders of magnitude, and the C-V hysteresis width is minimized by >75%, indicating enhanced oxide quality. These results are supported by high-resolution transmission electron microscopy and energy dispersive X-ray spectroscopy analysis, confirming the creation of an atomically well-defined interface in the Al2O3/H-Ge heterojunction with ACM vIL, even under high-temperature annealing conditions. Density functional theory calculations further clarify that ACM vIL preserves the hydrogen-passivated Ge surface without altering its electronic band structure. These results demonstrate that ACM vIL effectively improves the interface properties and enhances the oxide quality, enabling further advancements in ultrasmall-scale MOS devices.
Keywords: Amorphous carbon monolayer; Interface trap density; Interface-trap density; Metal oxide semiconductor; Metal-oxide semiconductor devices; Metal-oxide- semiconductorcapacitors; Metal-oxide-semiconductor interlayer; Semiconductor interfaces; Ultra-small; Van der Waal; amorphous carbon monolayer; interface trap density; MOS capacitors; MOS interlayer; semiconductor interface